Os desafios político-jurídicos do Brasil no combate à desinformação no twitter e facebook a partir do período da pandemia de covid-19 - Witschoreck, Pedro Victor dos Santos (2022)
Information and Communication Technologies (ICTs) are revolutionary in relation to many fundamental rights, among them the right of information and free speech. This fact implies the emergence of many political-legal challenges to combat disinformation that circulates the environment provided from the ICTs, such as Twitter and Facebook. For such reason, the present essay had the goal to study which are the challenges in the theme on the Covid-19 pandemic’s context. For this, issues were analyzed such as freedom of speech and the right of information in relation to the architecture and dynamic of Twitter and Facebook social media. From this general understanding, the research issue was to investigate what are the main Brazil’s political-legal challenges related to disinformation on Twitter and Facebook social media from the period of the Covid-19 pandemic, considering the combat among the public sphere versus private sphere. From this point, the idea was to investigate which are the main existent difficulties around the legitimacy to fight against disinformation during the pandemic period, reason why it matters to check the contradictions of the main bill in progress and give the general prospect of what the other bills seek to propose. Also, it was essential to evaluate how the Federal Government dealt with the pandemic in relation to information, that is also a legitimacy problem, once the state agents and people responsible for the elaboration of regulamentation themselves are the responsible of disinformation. From this matter, possible ways to assuage public health disinformation were investigated. For this, it was approached specifically how Brazil behaved considering the Access to Information Law (AIL) once it represents the institutional path to obtain many answers about the pandemic. Path that was violated many times. The essay was elaborated by the hypothetic-deductive method of monographic and comparative procedures and bibliographic and documental research. Having that said, the last stage pointed the found challenges, analyzed them once more in the sense of reaching the best conclusion between regulation or exclusively law regulamentation in the search to respond the hypothetical perspective. As a result of the research, regulation was confirmed as the best hypothesis because it involves many agents of the public and private sceneries and the civil society. Besides, regulation itself allows dialogue among all the departments, allows self-regulation, public regulation, and co-regulation, all depending on the situation in evidence and the established scenario.